Quantifying species contributions to ecosystem processes: a global assessment of functional trait and phylogenetic metrics across avian seed-dispersal networks - Pigot,AL; Bregman,T; Sheard,C; Daly,B; Etienne,RS; Tobias,JA (Proceedings of the Royal Society B: Biological Sciences, 2016)
Quantifying the role of biodiversity in ecosystems not only requires understanding the links between species and the ecological functions and services they provide, but also how these factors relate to measurable indices, such as functional traits and phylogenetic diversity. However, these relationships remain poorly understood, especially for heterotrophic organisms within complex ecological networks. Here, we assemble data on avian traits across a global sample of mutualistic plant–frugivore networks to critically assess how the functional roles of frugivores are associated with their intrinsic traits, as well as their evolutionary and functional distinctiveness. We find strong evidence for niche complementarity, with phenotypically and phylogenetically distinct birds interacting with more unique sets of plants. However, interaction strengths—the number of plant species dependent on a frugivore—were unrelated to evolutionary or functional distinctiveness, largely because distinct frugivores tend to be locally rare, and thus have fewer connections across the network. Instead, interaction strengths were better predicted by intrinsic traits, including body size, gape width and dietary specialization. Our analysis provides general support for the use of traits in quantifying species ecological functions, but also highlights the need to go beyond simple metrics of functional or phylogenetic diversity to consider the multiple pathways through which traits may determine ecological processes.